Kekuatan Pembuktian Sertifikat Hak atas Tanah sebagai Alat Bukti dalam Perkara Perdata - I Kadek Edy Gunawan; A.A Sagung Laksmi Dewi; Luh Putu Suryani (Warmadewa Press, 2020)
The land is very important for human life. Land problems often occur which still exist from ancient times until now. This research was conducted with the aim of describing how a certificate as proof of ownership of land rights can provide legal protection for people and legal entities as rights holders and whether the land title certificate must be supported by other evidence in its proof. The research method used is normative legal research with the approach of applicable laws and regulations. The results of this study indicated that in land disputes in court proceedings, certificates as proof of ownership can be used by judges to strengthen evidence to seek the truth. In proving an event or legal relationship, it must be supported by the existence of the truth or right. One way to do this is by submitting something that contains a reading sign in certain forms made by an authorized official. Furthermore, a certificate of ownership of land as a means of written evidence in a civil case examination can be proven by other means of evidence in which according to the judge's judgment it turns out that the evidence has perfect evidence strength and the statements contained in the certificate are proven to be incorrect.